Gender Representation in the Verbal and Visual Content of Arabic Textbooks: A Critical Content Analysis Study at STAIN Sultan Abdurrahman Kepulauan Riau - Aidillah Suja; Renti Yasmar; Ahmad Naweed Rahimi khamosh; Shifa Marwah Mu'afa; Taskiya Rumaisha Hanifa; Addina Silmi Khairun Nisa (Diwan Media Pustaka, 2026)
This study investigates gender representation in the verbal and visual texts of Arabic textbooks used at STAIN Sultan Abdurrahman Kepulauan Riau, namely Al-Lughah al-‘Arabiyyah al-Rā’i‘ah lil-Mubtadi’īn 1 and 2. The study employed a critical content analysis approach to examine how gender is constructed through both visual and verbal elements in the textbooks. Visual data were analyzed through four indicators: pictures that only included men or women, foregrounded male/female figures in relation to backgrounded ones, pictures of boys and girls, and visual contexts identified as domestic or professional. Verbal data were analyzed through three indicators: men and women as subjects, objects, and possessives in sentences. The findings reveal that male representation remains dominant across both dimensions. In the visual texts, men were more visible, more frequently foregrounded, and more often represented as children than women. In the verbal texts, men also appeared more frequently as subjects, objects, and possessive forms in sentence structures. These findings indicate that gender bias in the textbooks operates simultaneously at both visual and verbal levels. The study confirms that Arabic textbooks function not only as pedagogical tools but also as ideological media that may reproduce gendered power relations. Therefore, the development of Arabic teaching materials in Islamic higher education needs to be more responsive to gender-inclusive and equitable representation.